Membangun Karakter Pemuda Peduli Lingkungan Dalam Pariwisata Berkelanjutan Di Kota Bengkulu - Askani, Askani; Fatmala , Rizki Ade; Saputra , Defo Dian; Angglena , Deva; Faris, Sakut Amin Al (Jurnal Kewirausahaan dan Bisnis, 2021)
Sustainable tourism is increasingly becoming a key focus in the development of cities in Indonesia, including in Bengkulu City. This research aims to explore the role of youth in building environmental stewardship character in the context of sustainable tourism in Bengkulu City. Qualitative research methods were used in this study, involving in-depth interviews with local youth, tourism stakeholders, and the environmental community. The results showed that youth have great potential in influencing sustainable tourism practices through their role as social change agents. Youth in Bengkulu City show high concern for the environment, but still need more support and awareness of the importance of sustainable tourism practices. Factors such as education, access to information, and active participation in local activities play a key role in the character building of environmentally concerned youth. These findings have important implications for the development of programs and policies aimed at encouraging the active role of youth in supporting sustainable tourism in Bengkulu City. Strengthening cooperation between the government, tourism industry, and civil society is necessary to create a conducive environment for the growth of environmentally concerned youth characters.